1984
DOI: 10.1038/309255a0
|View full text |Cite
|
Sign up to set email alerts
|

Formation of germ-line chimaeras from embryo-derived teratocarcinoma cell lines

Abstract: The recent availability in culture of embryo-derived pluripotential cells which exhibit both a normal karyotype and a high differentiative ability has encouraged us to assess the potential of these cells to form functional germ cells following their incorporation into chimaeric mice. We report here the results of blastocyst injection studies using three independently isolated XY embryo-derived cell lines (EK. CP1 , EK. CC1 .1 and EKCC1 .2) which produce a very high proportion (greater than 50%) of live-born an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
654
2
29

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,377 publications
(688 citation statements)
references
References 17 publications
3
654
2
29
Order By: Relevance
“…Several studies comparing naïve and primed pluripotent stem cells have indicated that the two types of cells exhibit different molecular and functional properties, including colony morphologies, single-cell passage abilities [7,8], dependent signaling pathways [6,9,10], pluripotent gene expression profiles, and, most important, mouse embryo integration capacity to generate cross-species chimeras [7,11,12]. Previous studies have also suggested that human primed iPSCs and mouse EpiSCs can be converted to the naïve ground state via chemical manipulation or the overexpression of specific transcription factors [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies comparing naïve and primed pluripotent stem cells have indicated that the two types of cells exhibit different molecular and functional properties, including colony morphologies, single-cell passage abilities [7,8], dependent signaling pathways [6,9,10], pluripotent gene expression profiles, and, most important, mouse embryo integration capacity to generate cross-species chimeras [7,11,12]. Previous studies have also suggested that human primed iPSCs and mouse EpiSCs can be converted to the naïve ground state via chemical manipulation or the overexpression of specific transcription factors [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…One aspect in this long multistep process that has not been streamlined with regard to the logistics and ethics of mouse breeding is the efficiency or rate of germline transmission (GLT): the transmission of the ES cell‐derived genome through the germline of male chimeras to their offspring (Bradley et al ., 1984). Such chimeras are referred to as germline chimeras.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the development of mouse embryonic stem (ES) cells 1,2 and a variety of mutagenic technologies [3][4][5][6][7][8][9][10][11][12] , it is now possible to plan a systematic assault on the mouse genome to document function. The most straightforward way to start this program is to create and characterize null alleles in the germ line.…”
mentioning
confidence: 99%